Design, validation and application of an unobtrusive oar forceangle measurement system - Turner, T.; Gravenhorst, F.; Draper, C.; Smith, R. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Feedback is necessary for the improvement of motor performance. Elite level athletes in particular require accurate and detailed kinematic and kinetic information for improvement. The purpose of this study was to design, build, validate and apply an unobtrusive oar force-angle measurement system for the evaluation of on-water rowing performance. Performance measurement systems must also meet the criteria of accuracy, unobtrusiveness, reliability, quality visualisation and affordability. Using high quality IMU and force measurement technology a system (RowIMU) was designed and built that met these criteria. Results for horizontal, vertical and feather angle of the oar and the normal handle force were obtained and reported. The system provided innovative and useful information for coaches and rowers.